A Design of Experiment-based Approach for the Formulation Development and Evaluation of Repaglinide Transdermal Patch Using Natural Polymers - Chauhan, Rajendra (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The main aim of this study was to Formulation and Characterization of Repaglinide Transdermal Patch Using Natural polymers. Materials and Methods: The Box–Behnken design was used, which has three levels and three factors to investigate the associate impact of significant attributes on tensile strength, In vitro drug release, and Ex vivo drug permeation. Fifteen formulations were developed that differed in the polymer ratio (9:1, 8:1, and 7:1). The permeation of repaglinide through hairless goat ear skin through Ex vivo was found to increase with the help of permeation enhancer d-limonene. Results: As per the experimental data, it is concluded that the R12 is the best formulation in ex vivo permeation, in which we have taken 30% propylene glycol as a plasticizer, 3% d-limonene as a permeation enhancer, and this formulation shown 301.825 μg/cm2 permeation in 24 h. Conclusion: After optimizing all formulations, it concluded that the ratio of polymer in 9:1, 3% of a permeation enhancer, and 30% plasticize was the optimum quantity of different excipients used in the optimized formulation. These findings suggest that transdermal repaglinide delivery may have therapeutic promise, with benefits such as reduced dose frequency, better patient compliance, non-invasive properties, enhanced bioavailability, and ease of medication discontinuation.